Approche cartographique de l’évolution du trait de côte dans l’estuaire de la Casamance - Mamadou Thior; Amadou Abou Sy; Idrissa Cisse; El Hadji Balla Dieye; Tidiane Sane; Boubacar Demba Ba; Boubacar Solly; Luc Descroix (M@ppemonde)
This article offers a cartographical and statistical approach to calculating rate variance of coastlines over time using the DSAS plugin; using the northern part of Casamance estuary in Senegal as the case study. To do so, we established a method to stasticially extrapolate and calculate trends, based on the analyis of Landsat satellite images taken between 2004 and 2019. We were thus able to obtain a cartographic and graphic representation of statistical results concerned with the changing coastline of the Casamance estuary.